At the intersection of education, art and activism: The case for Creative Chemistries. Issue 2 (1st June 2017) - Hamlin, Jessica
The work of many contemporary artists includes the use of dialogue and socially engaged practices. Interdisciplinary exchange, community building and participatory dialogue have been at the core of progressive education since the turn of the century. Inspired by the notion of the artist and the educator as creative 'border crossers, ' this article describes a unique experiment in sharing creative practices in the arts and education that took place at the Park Avenue Armory in New York City in November 2015 by the non-profit organization Art21. Creative Chemistries was conceived as a means of placing artists, classroom teachers, students, principals, museum educators and community organizers, policy-makers in education, representatives from community-based arts organizations and university faculty all at the same table to talk and make work together exploring the intersections and disconnects between the values framing their labour and creative practices. This narrative proposes that forms of intentional interdisciplinary dialogue should be considered an activist gesture, and highlights the voices of Creative Chemistry participants to describe the new thinking, learning and creative practices generated between them.